2017
DOI: 10.1523/jneurosci.3300-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral Occipital Cortex Is Selective for Object Shape, Not Texture/Color, at Six Months

Abstract: Understanding how the human visual system develops is crucial to understanding the nature and organization of our complex and varied visual representations. However, previous investigations of the development of the visual system using fMRI are primarily confined to a subset of the visual system (high-level vision: faces, scenes) and relatively late in visual development (starting at 4 -5 years of age). The current study extends our understanding of human visual development by presenting the first systematic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…The human ventral occipitotemporal cortex (VOTC) has a well established medial-to-lateral arrangement of category-selectivity bilaterally (Grill-Spector and Malach, 2004) and a clearly-defined pattern as a function of eccentricity (Hasson et al, 2002). This selectivity and topography appear to emerge early in life, revealed by both fMRI (Scherf et al, 2007;Golarai et al, 2017;Barttfeld et al, 2018;Dehaene-Lambertz et al, 2018) and functional nearinfrared spectroscopy studies (Otsuka et al, 2007;Emberson et al, 2017), and then be refined further over development (Nishimura et al, 2015;Deen et al, 2017). The correspondence between this cortical arrangement and perceptual behavior, and the extent to which this relationship is malleable, remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The human ventral occipitotemporal cortex (VOTC) has a well established medial-to-lateral arrangement of category-selectivity bilaterally (Grill-Spector and Malach, 2004) and a clearly-defined pattern as a function of eccentricity (Hasson et al, 2002). This selectivity and topography appear to emerge early in life, revealed by both fMRI (Scherf et al, 2007;Golarai et al, 2017;Barttfeld et al, 2018;Dehaene-Lambertz et al, 2018) and functional nearinfrared spectroscopy studies (Otsuka et al, 2007;Emberson et al, 2017), and then be refined further over development (Nishimura et al, 2015;Deen et al, 2017). The correspondence between this cortical arrangement and perceptual behavior, and the extent to which this relationship is malleable, remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Infants as young as 4.5 months have been found to individuate objects using their shape, months before the ability to individuate objects based on their patterns or colors is demonstrated (Wilcox, 1999). And it has been shown that infants as young as 6 months are already equipped with a region of their brain selectively activated to changes in shape (Emberson, Crosswhite, Richards, & Aslin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Research over the past two decades has indicated that cortical areal formation follows a unique, spatiotemporal time-lapse sequence during childhood and through early adulthood (Gogtay et al, 2004) with different maturational trajectories for different areas and some regions not fully mature until well into adolescence. For example, face-selective cortex follows a slower developmental trajectory, not fully mature even in early adulthood (Germine et al, 2011), compared to object-selective cortex, which may be adult-like as early as age 5 (Gogtay et al, 2004; Golarai et al, 2015, 2010, 2007; Haist et al, 2013; Scherf et al, 2011, 2007) or even younger (Emberson et al, 2017; Nishimura et al, 2015). The pattern of word selectivity in the VWFA also emerges slowly over development, as reading and writing experience accumulate (Maurer et al, 2006), and orthographic representations may develop at the expense of face representations in the LH (Cantlon et al, 2011; Dehaene et al, 2015; Dundas et al, 2013).…”
Section: Plasticity In Higher-order Visual Cortexmentioning
confidence: 99%